The Influence of YouTube Influencer Attributes on Information Credibility and Purchase Intention in Malaysia: The Mediating Effect of Consumer Information Adoption - Nazer Mohamed, Nurashikin; Jaafar, Norizan (Gadjah Mada International Journal of Business, 2026)
Consumers are placing greater trust in influencers for information about products and services, appreciating the authenticity of their personal experiences. In Malaysia, women are particularly drawn to beauty influencers on YouTube, trusting their recommendations for cosmetic products. This study seeks to examine the impact of influencer characteristics on the perceived credibility of information and how this, in turn, shapes Malaysian women's adoption of information and purchasing decisions regarding cosmetics. Data were gathered through an online survey utilising purposive and snowball sampling techniques, resulting in 393 responses available for analysis. Structural Equation Modelling (SEM) was conducted utilising IBM SPSS AMOS version 24.0. Findings indicate that the individual traits of influencers significantly influence the credibility of the information they provide. Additionally, information credibility is shown to have a direct effect on both the adoption of information and consumers’ purchase intentions, with information adoption further directly influencing purchase intentions. The study highlights the critical importance of information credibility in connecting influencer attributes with consumers’ willingness to adopt information and make purchases, offering actionable insights for marketers aiming to maximise the effectiveness of social media influencer collaborations.